2010
DOI: 10.1155/2010/502564
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tert-Butylhydroquinone on Intestinal Inflammatory Response and Apoptosis following Traumatic Brain Injury in Mice

Abstract: Traumatic brain injury (TBI) can induce intestinal inflammatory response and mucosal injury. Antioxidant transcription factor nuclear factor erythroid 2-related factor 2 (Nrf2) has been shown in our previous studies to prevent oxidative stress and inflammatory response in gut after TBI. The objective of this study was to test whether tert-butylhydroquinone (tBHQ), an Nrf2 inducer, can protect against TBI-induced intestinal inflammatory response and mucosal injury in mice. Adult male ICR mice were randomly divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
31
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 36 publications
6
31
0
Order By: Relevance
“…As such, decreased NF-κB activity partially explains the anti-inflammatory effect of tBHQ in the present study. These findings are consistent with previous studies showing that tBHQ or sulforaphane decrease NF-κB activation, production of inflammatory cytokines (TNF-α, IL-1β, and IL-6), COX-2 expression, and PGE2 release in vivo and in vitro (Heiss et al , 2001; Jin et al , 2010; Khodagholi and Tusi, 2011; Koh et al , 2009). However, to the best of our knowledge, the present study is the first to report the protective role of Nrf2 activation on toxicant-stimulated inflammatory responses in human placental cells.…”
Section: Discussionsupporting
confidence: 93%
“…As such, decreased NF-κB activity partially explains the anti-inflammatory effect of tBHQ in the present study. These findings are consistent with previous studies showing that tBHQ or sulforaphane decrease NF-κB activation, production of inflammatory cytokines (TNF-α, IL-1β, and IL-6), COX-2 expression, and PGE2 release in vivo and in vitro (Heiss et al , 2001; Jin et al , 2010; Khodagholi and Tusi, 2011; Koh et al , 2009). However, to the best of our knowledge, the present study is the first to report the protective role of Nrf2 activation on toxicant-stimulated inflammatory responses in human placental cells.…”
Section: Discussionsupporting
confidence: 93%
“…In kidney, tBHQ protected against ischemia-reperfusion injury [43]. Moreover, a recent study showed that tBHQ administration suppressed the intestinal inflammation and reduced the mucosal damage following traumatic brain injury [44]. Our study was initially designed to test this hypothesis using tBHQ as an Nrf2 inducer in AML-12 cells, a non-transformed murine hepatocyte cell line.…”
Section: Discussionmentioning
confidence: 99%
“…However, upon exposure to oxidative stress, Nrf2 is released from Keap1, translocates into the nucleus, and stimulates antioxidant response element (ARE)-dependent phase II gene expression891011. Preliminary studies in our laboratory explored the protection of Nrf2 in traumatic brain injury1213141516. An increasing number of studies supporting the pivotal role of Nrf2 in angiogenesis show that Nrf2 may promote vascular development via protection of retina from hyperoxia-induced oxidative stress17; these studies also indicate that Nrf2 blockade suppresses tumor cell angiogenesis and migration in vivo and in vitro 181920.…”
mentioning
confidence: 99%